Breaching and Bridging: The journey from the tragicomedy of existence to the therapeutic encounter and back (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
This article explores the tragicomic nature of human existence, emphasising the interplay between rupture and repair within life's unpredictable narrative. Drawing from philosophical reflections, it attempts to describe the constant cycle of breaching and bridging, within the therapeutic encounter as well.
Keywords: Bridge as process; breaches and raptures; tragicomedy of life; therapeutic encounter; presence